Financing Smart Local Energy Systems: A Conceptual Framework and Research Agenda - Fuentes-Gonzalez, F (Elsevier Ltd, 2025)
Smart local energy systems (SLES) are expected to contribute to meeting net zero carbon emission targets, as well as enabling energy decentralisation, democratisation and digitalisation. There are, however, unresolved questions about finance. We extend the existing corporate governance and risk management model CLASS to a new CCLLASS model. The model is used to explore pathways to SLES investment through securitising future cash flows. Case study evidence is used to explore governance and risk management practices suited to building investor confidence in securitisation. Several governance and risk management measures already in place support implementation and operation of securitisation, and should strengthen investor confidence. There is however scope for improvement in several elements, including final market architecture and explicit characterisation of benefits to localities. Further research is needed to test feasibility of a SLES future cash flow securitisation mechanism, including quantitative asset aggregation and systematic comparison of securitisation and other financial instruments. © 2024 Elsevier Ltd